Of Experience and Being: Apropos of This and That - An Analysis from Daoism to Heidegger - Shea Divoll, (Dianoia: The Undergraduate Philosophy Journal of Boston College, 2025)
Martin Heidegger’s Being and Time presented a rather novel view of ontology with a set of unique concepts. Conventionally, the work of Heidegger is considered as definitively Western, and yet, beneath the surface, it is well-supported that Heidegger was notably influenced by both Chinese and Japanese ideas. In this thesis, I will argue that the extent to which classical Daoist sources have appeared in Martin Heidegger’s work, especially Being and Time, has hitherto been overlooked; and furthermore I will set the stage for how classical Daoist ideas like wuwei manifest in a relationship with Dasein. Finally, I will demonstrate the similarity of the paradigms Heidegger and classical Daoist thinkers each employ regarding tooling, equipmentality, and Thrownness.